Speciation in the exposed intertidal zone: the case of Saccharina angustissima comb. nov. & stat. nov. (Laminariales, Phaeophyceae). Issue 1 (1st January 2018) - Augyte, Simona; Lewis, Louise; Lin, Senjie; Neefus, Christopher D.; Yarish, Charles
Abstract: Saccharina latissima is a perennial kelp with a circumboreal distribution from the North Pacific to the North Atlantic coasts. Our study clarified the taxonomy of the morphologically distinct Saccharina latissima forma angustissima (Collins) A.Mathieson from the low intertidal zone on exposed islands and ledges of Casco Bay, Maine, USA. To identify genetic divergence between the two morphotypes, S. latissima and S. latissima f. angustissima, we used a multilocus phylogenetic approach including nuclear-encoded internal transcribed spacer, mitochondrial cox 1 and cox3, and plastid-encoded rbc L gene sequences. Genetic analysis of the individual markers and combined data set using SVDquartets resulted in p-distance values for all markers of < 1%, suggesting low divergence between the two forms. However, there was as much or more genetic divergence between S. latissima and S. latissima f. angustissima as there were between other taxonomically accepted species of Saccharina . To investigate sexual compatibility between the two forms, we made reciprocal crosses of the gametophytes and observed sporophyte formation. All crosses were successfully grown to the juvenile sporophyte stage, suggesting that the two are reproductively compatible in vitro . It is unknown if the two populations freely hybridize in the field. Last, we compared wave action, the ecological factor most likely driving the unique morphology, at exposed sites with S. latissima f. angustissima and protected sites with S. latissima . The mean wave force at the exposed site was over 30 times higher in magnitude than at the protected site at 160.04 ± 32.58 N and 4.75 ± 6.75 N, respectively, during the summer. The significant differences in morphology, the lack of specimens with intermediate morphologies, and the results of a common garden experiment suggest that the morphological differences in S. latissima f. angustissima are heritable with a genetic basis. Therefore, on the basis of our molecular evidence coupled with ecological studies, we are elevating S. latissima f. angustissima (Collins) A.Mathieson to specific rank as S. angustissima (Collins) Augyte, Yarish & Neefus comb. nov . & stat. nov .